Characterizations of -Continuous Mappings in Ideal Topological Spaces - Kalaivani, N.; Narmada Devi, R.; Gunasekar, T. (International Journal of Engineering and Technology, 2018)
In this paper the notion of -Continuous Mappings is introduced and some of their properties are studied. Further the concept of contra -Continuous Mappings and(Î³Î±, Î²)-I-Continuous Mappings are introduced and properties are analyzed.Â Â